Comparison of high latitude electron density profiles obtained with the GPS radio occultation technique and EISCAT measurements. - Stolle, C.; Rietveld, Michael T.; Jakowski, N.; Schlegel, K: (European Geosciences Union, 2004)
To obtain a comprehensive view on high latitude processes by applying different observation techniques, the SIRCUS campaign was initiated in 2001/2002. This paper compares electron density profiles derived from CHAMP radio occultation data and those measured with the EISCAT facility. Since ionospheric profiling with the help of space-based received GPS is a relatively new technique, validations with established independent instruments are of crucial need. We present 28 profiling events for quasi-statistical analyses, which occurred during the SIRCUS campaigns and describe some of them in more detail. We found out that the majority of profile comparisons in electron density peak value and height, as well as in TEC, lie within the error ranges of the two methods. Differences in the ionospheric quantities do not necessarily occur when the locations of the occultation and of the radar site show considerable distances. Differences are more pronounced when the ionosphere is remarkably structured.